IMPLMENTASI METODE DISKUSI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA SEBAGAI PENGUATAN KARAKTER PADA MURID KELAS III SD NEGERI 1 BUNGBUNGAN KLUNGKUNG - Bayu Juniarta, I Komang Agus; Sueca, I Nyoman; Suryawan, I Gde (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of the discussion method in elementary education is considered to be in line with children's developmental characteristics at the concrete operational stage. The use of the discussion method in Pancasila Education is essential because the learning process focuses not only on understanding knowledge but also on developing students’ attitudes and character. This study aims to explore and analyze students’ attitudes, knowledge, and life skills through the implementation of the discussion method in Pancasila Education learning from a comprehensive educational perspective. This study employed a qualitative research approach with a descriptive qualitative design. Data were collected through observation, interviews, and documentation. The collected data were analyzed using data reduction, data display, and conclusion drawing/verification techniques. The findings of the study reveal that: (1) the implementation of the discussion method in Pancasila Education learning for third-grade students was carried out through several stages, namely planning, implementation, and evaluation; (2) teachers’ efforts in implementing the discussion method were conducted through the use of interactive learning strategies, the cultivation of habits and character values, and the contextualization of learning materials with students’ real-life experiences; and (3) the discussion method had a positive impact on students’ cognitive and affective understanding, character formation, and social skills development. Therefore, the discussion method can be considered an effective learning strategy for strengthening students’ character while enhancing active participation and meaningful learning experiences in Pancasila Education. Keywords: Discussion Method, Pancasila Education, Character Education.